Literatury staropolskiej „budowa ciała” i „usposobienie, temperament” - Obremski, Krzysztof (Przestrzenie Teorii, 2020)
The text is a review of the Dariusz Śnieżko’s book Kompleksja literatury. Studia staropolskie (The Complexion of Literature. Old-Polish Studies) (TAiWPN UNIVERSITAS, Krakow 2019). The only serious doubt regards the sound of the title (readers might not know the word “complexion”). Kompleksja literatury is a fascinating book. For whom? – certainly students of Old-Polish literature (and it will be also inspiring for scholars of the next historical and literary epochs). What? – revealing the most important dimensions of Old-Polish literature. Why? – because in works published so far the scant use of source texts proves to be representative of the most general material remaining of Old-Polish literature in its intertwining of anthropology and dialectics of orality and literacy.